The Epilepsy of Infancy With Migrating Focal Seizures: Identification of de novo Mutations of the KCNT2 Gene That Exert Inhibitory Effects on the Corresponding Heteromeric KNa1.1/KNa1.2 Potassium Channel - Mao, Xiao; Bruneau, Nadine; Gao, Quwen; Becq, Hélène; Jia, Zhengjun; Xi, Hui; Shu, Li; Wang, Hua; Szepetowski, Pierre; Aniksztejn, Laurent (Frontiers in Cellular Neuroscience, 2020)
Epilepsy of Infancy with Migrating Focal Seizures (EIMFS) (previously called Malignant migrating partial seizures of infancy) are early-onset epileptic encephalopathies (EOEE) that associate multifocal ictal discharges and profound psychomotor retardation. EIMFS have a genetic origin and are mostly caused by de novo mutations in the KCNT1 gene, and much more rarely in the KCNT2 gene. KCNT1 and KCNT2 respectively encode the KNa1.1 (Slack) and KNa1.2 (Slick) subunits of the sodium dependent voltage gated potassium channel KNa. Functional analyses of the corresponding mutant homomeric channels in vitro suggested gain-of-function effects. Here we report two novel, de novo truncating mutations of KCNT2: one mutation is frameshift (p.L48Qfs43), is situated in the N-terminal domain, and was found in a patient with EOEE (possibly EIMFS); the other mutation is nonsense (p.K564*), is located in the C-terminal region, and was found in a typical EIMFS patient. Using whole cell patch-clamp recordings, we have analyzed the functional consequences of those two novel KCNT2 mutations on reconstituted KNa1.2 homomeric and KNa1.1/KNa1.2 heteromeric channels in transfected CHO cells. We report that both mutations significantly impacted on KNa function; notably they decreased global current density of heteromeric channels by ~25% (p.K564*) and ~55% (p.L48Qfs43). Overall our data emphasize the involvement of KCNT2 in EOEE and provide novel insights into the role of heteromeric KNa channel in the severe KCNT2-related epileptic phenotypes. This may have important implication regarding elaboration of future treatment.